Application of Six Sigma (Dmaic) Method to Reduce Defect Amount in Assembly Process A Case Study PT. XYZ - Warinah, Warinah; Nusraningrum, Dewi (International Humanities and Applied Science Journal, 2019)
PT. XYZ is a company engaged in industry and manufacturing in the manufacture of sports shoe products. The company has a very high defect in the assembly process seen in the defective rate report from January 2017 to August 2018. The purpose of this study is to reduce the number of defects in the assembly process using the Six Sigma (DMAIC) method. The results showed that there were 5 dominant types of defects related to Critical To Quality (CTQ), namely Undercement, Dirty shoes, Unpairing-heel height, Broken stitching and Quarter wrinkles. Furthermore, an analysis of the causes of defects is carried out by using cause and effect diagrams and an improvement effort using 5W + H analysis. The results of efforts to decrease the number of defects in the assembly process using the DMAIC method show that the DPMO value for these five CTQ defects decreased to 2056 PPM from 3898 PPM or decreased by 47.3%. Whereas for the value of the sigma level obtained 4.39 Ïƒ from 4.16 Ïƒ